ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA SEKTOR INDUSTRI PENGOLAHAN PADA 17 KABUPATEN/KOTA DI JAWA BARAT - Sya'bana, Arya; Al Muizzuddin Fazaalloh (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
This study aims to determine the effect of the GRDP of the manufacturing sector, UMK, FDI, DDI and HDI on employment in the manufacturing sector in 17 District/Cities of West Java 2014 – 2022. This type of research is quantitative using panel data, namely 17 districts/Cities in West Java in 2014 – 2022. The analytical method used is panel data regression analysis, with the estimation model used is the Fixed Effect Model. The results of this study partially UMK has a significant negative effect on employment in the manufacturing sector, HDI has a significant effect on employment in the manufacturing sector. while the GRDP of the manufacturing sector, FDI, and DDI have no significant effect on employment in the manufacturing sector. Simultaneously, all independent variables have a significant effect on employment in the manufacturing sector in 17 districts/cities of West Java.